An Analysis of Financial statements of State Bank of India from 2014 to 2019------ - RAJU, Dr.K.V.V.; REDDY, Y DEVENDRA (The journal of contemporary issues in business and government, 2023)
This article is about analysis of financial statements of SBI from 2014 to 2019. The financial tools used are Common Size, Comparative, Trend and Ratio analysis. The objective of the paper is to find out and examine the financial performance of the biggest and sound bank in India. The graphs and analysis made with some positive conclusions.